Chemical pesticides : - Stenersen, Jorgen (CRC Press, 2004)
Environmental-friendliness, issues of public health, and the pros and cons of genetically-modified crops all receive regular coverage in the world's media. This, in turn, has led to increased questioning and investigation of chemical pesticides.Stenersen's concise introduction to chemical pesticides describes these compounds according to their biochemical mode of action, such as whether they are enzyme inhibitors, receptor ligands, or free radical generators. Chemical Pesticides provides answers to why pesticides are toxic to the target organism, how resistance develops, why pesticides are toxic to some organisms and not others. The book also discusses legal matters and concerns as well as potential environmental problems.